Volumetric Analysis of Chronic Maxillary Atelectasis. Issue 3 (May 2015) - Lin, Giant C.; Sedaghat, Ahmad R.; Bleier, Benjamin S.; Holbrook, Eric H.; Busaba, Nicolas Y.; Yoon, Michael K.; Gray, Stacey T.
Background: The relationship between orbit and maxillary sinus volumes in patients with chronic maxillary atelectasis (CMA), commonly known as silent sinus syndrome if enophthalmos is present, is poorly understood. Methods: A retrospective review of 22 patients who underwent endoscopic sinus surgery (ESS) for CMA from 2005 to 2013 was performed. Computed tomography (CT) images were analyzed using OsiriX 5.8.2 software for volumetric analysis of the orbit and maxillary sinus at presentation and after surgical treatment with ESS. Results: Pretreatment mean orbit volumes on the diseased side (DS) and the contralateral side (CS) were 29.22 and 26.50 mL, respectively (p < 0.001); mean sinus volumes on the DS and CS were 8.51 and 17.20 mL, respectively (p < 0.001); and pretreatment mean midorbit heights (MOHs) on the DS and CS were 3.39 cm and 3.07 cm, respectively (p < 0.001). The percent decrease in sinus volume on the DS compared to that on the CS did not correlate significantly with the percent orbit-volume increase. Enophthalmos was present in nine (41%) patients, and diplopia was present in three (14%) patients. The measured degree of increased orbit volume and decreased sinus volume secondary to CMA did not significantly predict the presence of enophthalmos at presentation. Seven patients underwent sinus CT more than 6 months after ESS. In these patients, orbit volume on the DS decreased from 29.67 to 27.52 mL (p = 0.005), and sinus volume on the DS increased from 9.78 to 11.84 mL (p = 0.08). Conclusions: Volumetric analysis is a powerful and novel method for objectively demonstrating the degree of orbit expansion and maxillary sinus contraction seen with CMA. Spontaneous maxillary sinus expansion and a decrease in orbit volume can occur after ESS, but post-ESS volumes do not return to the normal volume of the CS.